Species limits in the genus Thamnistes (Aves: Passeriformes: Thamnophilidae): an evaluation based on vocalizations - Isler, Morton L.; Whitney, Bret M. (Zootaxa, 2017)
The monotypic genus Thamnistes, consisting of the Russet Antshrike, T. anabatinus, is primarily a resident of foothills forests of the northern Andes and Middle America, extending to adjacent lowlands especially on the Pacific slope. Its vocalizations are somewhat poorly recorded as it is a participant in noisy mixed flocks of the lower canopy to the upper understory. In recent years, however, vocalizations of the Russet Antshrike have been recorded sufficiently to permit geographic analysis. Vocalizations supply valuable measures of species limits for antbirds because they are not learned. Our analysis revealed that the southernmost population was vocally distinct and is more appropriately considered a biological species: T. rufescens (Rufescent Antshrike). An additional population of the Russet Antshrike, T. a. aequatorialis, awaits further evaluation pending the acquisition of additional vocal recordings, morphological study, and genetic analysis.